Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
[tex]y=\frac { { { x }^{ 3 }\left( 2x+3 \right) }^{ \frac { 1 }{ 2 } } }{ { \left( x-2 \right) }^{ 2 } }[/tex]
[tex]\\ \\ { \left( x-2 \right) }^{ 2 }\cdot y={ x }^{ 3 }{ \left( 2x+3 \right) }^{ \frac { 1 }{ 2 } }[/tex]
[tex]\\ \\ \ln { \left( { \left( x-2 \right) }^{ 2 }\cdot y \right) } =\ln { \left( { x }^{ 3 }{ \left( 2x+3 \right) }^{ \frac { 1 }{ 2 } } \right) } [/tex]
[tex]\\ \\ \ln { \left( { \left( x-2 \right) }^{ 2 } \right) } +\ln { y } =\ln { \left( { x }^{ 3 } \right) } +\ln { \left( { \left( 2x+3 \right) }^{ \frac { 1 }{ 2 } } \right) }[/tex]
[tex]\\ \\ 2\ln { \left( x-2 \right) } +\ln { y } =3\ln { x } +\frac { 1 }{ 2 } \ln { \left( 2x+3 \right) }[/tex]
[tex]\\ \\ \ln { y } =3\ln { x } -2\ln { \left( x-2 \right) } +\frac { 1 }{ 2 } \ln { \left( 2x+3 \right) } [/tex]
[tex]\\ \\ \frac { 1 }{ y } \cdot \frac { dy }{ dx } =\frac { 3 }{ x } -\frac { 2 }{ x-2 } +\frac { 1 }{ 2x+3 }[/tex]
[tex]\\ \\ y\cdot \frac { 1 }{ y } \cdot \frac { dy }{ dx } =y\left( \frac { 3 }{ x } -\frac { 2 }{ x-2 } +\frac { 1 }{ 2x+3 } \right)[/tex]
[tex]\\ \\ \frac { dy }{ dx } =\frac { { x }^{ 3 }\sqrt { 2x+3 } }{ { \left( x-2 \right) }^{ 2 } } \cdot \left( \frac { 3 }{ x } -\frac { 2 }{ x-2 } +\frac { 1 }{ 2x+3 } \right)[/tex]
[tex]\\ \\ { \left( x-2 \right) }^{ 2 }\cdot y={ x }^{ 3 }{ \left( 2x+3 \right) }^{ \frac { 1 }{ 2 } }[/tex]
[tex]\\ \\ \ln { \left( { \left( x-2 \right) }^{ 2 }\cdot y \right) } =\ln { \left( { x }^{ 3 }{ \left( 2x+3 \right) }^{ \frac { 1 }{ 2 } } \right) } [/tex]
[tex]\\ \\ \ln { \left( { \left( x-2 \right) }^{ 2 } \right) } +\ln { y } =\ln { \left( { x }^{ 3 } \right) } +\ln { \left( { \left( 2x+3 \right) }^{ \frac { 1 }{ 2 } } \right) }[/tex]
[tex]\\ \\ 2\ln { \left( x-2 \right) } +\ln { y } =3\ln { x } +\frac { 1 }{ 2 } \ln { \left( 2x+3 \right) }[/tex]
[tex]\\ \\ \ln { y } =3\ln { x } -2\ln { \left( x-2 \right) } +\frac { 1 }{ 2 } \ln { \left( 2x+3 \right) } [/tex]
[tex]\\ \\ \frac { 1 }{ y } \cdot \frac { dy }{ dx } =\frac { 3 }{ x } -\frac { 2 }{ x-2 } +\frac { 1 }{ 2x+3 }[/tex]
[tex]\\ \\ y\cdot \frac { 1 }{ y } \cdot \frac { dy }{ dx } =y\left( \frac { 3 }{ x } -\frac { 2 }{ x-2 } +\frac { 1 }{ 2x+3 } \right)[/tex]
[tex]\\ \\ \frac { dy }{ dx } =\frac { { x }^{ 3 }\sqrt { 2x+3 } }{ { \left( x-2 \right) }^{ 2 } } \cdot \left( \frac { 3 }{ x } -\frac { 2 }{ x-2 } +\frac { 1 }{ 2x+3 } \right)[/tex]
y = ((x³)(2x + 3)^1/2)
(x - 2)²
y = ((x³)(√(2x + 3))
(x - 2)(x - 2)
y = ((√x^6)(√2x) + (√x^6)(√3))
(x² - 2x - 2x + 4)
y = ((√2x^7) + (√3x^6))
(x² - 4x + 4)
(x - 2)²
y = ((x³)(√(2x + 3))
(x - 2)(x - 2)
y = ((√x^6)(√2x) + (√x^6)(√3))
(x² - 2x - 2x + 4)
y = ((√2x^7) + (√3x^6))
(x² - 4x + 4)
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.